2011
DOI: 10.4306/pi.2011.8.4.362
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Are Decreased in Obsessive-Compulsive Disorder: Preliminary Investigation

Abstract: ObjectiveThere has been no study in the literature evaluating total blood count in obsessive-compulsive disorder (OCD). Therefore, we performed the present study to spesifically measure serum total blood count particularly white blood cells to see whether or not its eventual alterations might have an etiopathogenetic significance in patients with OCD.MethodsTotal blood count was measured in thirty patients and same number of healthy controls. Additionally, all patients were assessed by Yale-Brown Obsession Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
(8 reference statements)
1
16
1
Order By: Relevance
“…In the study evaluating hemogram parameters in adults with OCD, Atmaca et al reported that there were no significant differences between groups regarding hemogram parameters except neutrophil count. In this study, there was no difference between lymphocyte counts while neutrophil counts were low (33). In the study of Denny et al, there was no significant difference in hemogram parameters of OCD patients when compared to controls.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…In the study evaluating hemogram parameters in adults with OCD, Atmaca et al reported that there were no significant differences between groups regarding hemogram parameters except neutrophil count. In this study, there was no difference between lymphocyte counts while neutrophil counts were low (33). In the study of Denny et al, there was no significant difference in hemogram parameters of OCD patients when compared to controls.…”
Section: Discussioncontrasting
confidence: 41%
“…Inflammation plays a critical role in OCD etiology (10)(11)(12). HPA axis disorders, various cytokines, and cellular elements were investigated in various studies in this field (33,37). In the study investigating the HPA axis, Gustafsson et al showed a similar hypercortisolism in child and adolescent populations as previously demonstrated in adult OCD patients (23).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…NLR increased similarly as in depression but MPV decreased and these findings may reflect inflammation and role of inflammation in the complex pathophysiology of acute mania 21 . As a different psychiatric disorder group neutrophils were found to be decreased in obsessive compulsive disorder (OCD) in a study comparing CBC parameters between patients with OCD and healthy controls 24 .…”
Section: Discussionmentioning
confidence: 99%